Quantum Mechanics and the Philosophy of Alfred North Whitehead - Epperson, Michael (American Philosophy, 2004)
In Process and Reality and other works, Alfred North Whitehead struggled to come to terms with the impact the new science of quantum mechanics would have on metaphysics. This ambitious book is the first extended analysis of the intricate relationships between relativity theory, quantum mechanics, and Whitehead's cosmology. Michael Epperson illuminates the intersection of science and philosophy in Whitehead's work-and details Whitehead's attempts to fashion an ontology coherent with quantum anomalies. Including a nonspecialist introduction to quantum mechanics, Epperson adds an essential new dimension to our understanding of Whitehead-and of the constantly enriching encounter between science and philosophy in our century.